Investigating the role of somatic sequencing platforms for phaeochromocytoma and paraganglioma in a large UK cohort. (6th December 2021) - Winzeler, Bettina; Tufton, Nicola; S. Lim, Eugenie; Challis, Ben G.; Park, Soo‐Mi; Izatt, Louise; Carroll, Paul V.; Velusamy, Anand; Hulse, Tony; Whitelaw, Benjamin C.; Martin, Ezequiel; Rodger, Fay; et al.
Abstract: Objectives: Phaeochromocytomas and paragangliomas (PPGL) are rare neuroendocrine tumours with malignant potential and a hereditary basis in almost 40% of patients. Germline genetic testing has transformed the management of PPGL enabling stratification of surveillance approaches, earlier diagnosis and predictive testing of at‐risk family members. Recent studies have identified somatic mutations in a further subset of patients, indicating that molecular drivers at either a germline or tumour level can be identified in up to 80% of PPGL cases. The aim of this study was to investigate the clinical utility of somatic sequencing in a large cohort of patients with PPGL in the United Kingdom. Design and Patients: Prospectively collected matched germline and tumour samples (development cohort) and retrospectively collected tumour samples (validation cohort) of patients with PPGL were investigated. Measurements: Clinical characteristics of patients were assessed and tumour and germline DNA was analysed using a next‐generation sequencing strategy. A screen for variants within 'mutation hotspots' in 68 human cancer genes was performed. Results: Of 141 included patients, 45 (32%) had a germline mutation. In 37 (26%) patients one or more driver somatic variants were identified including 26 likely pathogenic or pathogenic variants and 19 variants of uncertain significance. Pathogenic somatic variants, observed in 25 (18%) patients, were most commonly identified in the VHL, NF1, HRAS and RET genes. Pathogenic somatic variants were almost exclusively identified in patients without a germline mutation (all but one), suggesting that somatic sequencing is likely to be most informative for those patients with negative germline genetic test results. Conclusions: Somatic sequencing may further stratify surveillance approaches for patients without a germline genetic driver and may also inform targeted therapeutic strategies for patients with metastatic disease.